2012
DOI: 10.1371/journal.pone.0034676
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoregulatory Mechanisms Underlying Prevention of Colitis-Associated Colorectal Cancer by Probiotic Bacteria

Abstract: Background Inflammatory bowel disease (IBD) increases the risk of colorectal cancer. Probiotic bacteria produce immunoregulatory metabolites in vitro such as conjugated linoleic acid (CLA), a polyunsaturated fatty acid with potent anti-carcinogenic effects. This study aimed to investigate the cellular and molecular mechanisms underlying the efficacy of probiotic bacteria in mouse models of cancer. Methodology/Principal Findings The immune modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 45 publications
2
54
1
Order By: Relevance
“…Bassaganya-Riera et al [75] (2012) studied the cellular and molecular mechanisms underlying the efficacy of probiotic bacteria in mouse models of inflammation-driven colorectal cancer. Immune cell subsets in the MLN, spleen and colonic lamina propria lymphocytes (LPL) were phenotypically and functionally characterized.…”
Section: Probiotic Strain Genes Involvedmentioning
confidence: 99%
See 1 more Smart Citation
“…Bassaganya-Riera et al [75] (2012) studied the cellular and molecular mechanisms underlying the efficacy of probiotic bacteria in mouse models of inflammation-driven colorectal cancer. Immune cell subsets in the MLN, spleen and colonic lamina propria lymphocytes (LPL) were phenotypically and functionally characterized.…”
Section: Probiotic Strain Genes Involvedmentioning
confidence: 99%
“…Inflammatory bowel disease Disfrutti et al [71] VSL#3 IL-10, TNFRSF1B Ghadimi et al [72] B. breve (DSMZ 20213) and L. rhamnosus GG IL-17 and IL-23 Grimoud et al [73] B. breve and L. lactis TLR-4 Chen et al [74] Saccharomyces boulardii VEGF Bassaganya-Riera et al [75] VSL#3 TNF-α, COX-2, and PPAR-γ Ulcerative colitis…”
Section: Table 2 Regulation Of Gene Expression By Probiotics In Inflamentioning
confidence: 99%
“…This suggests that sericin might have an effect on the function of cytotoxic T cells but it may not affect helper T cells. Despite the essential role of CD8 cell in anti-viral immunity, CD4 T cells can also play important roles for control of viral infection as well as cancer 26,27 . There was a reduction of CD80 positive cells without changes in CD86 positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…bulgaricus, which could inhibit colonocytes proliferation by inducing proapoptotic pathway by regulation of the concentration of COX-2 in colon. [137] Putaala et al demonstrated that the probiotics are involved in the inhibition of colon carcinogenesis by the downregulation of COX-2. [138] In another study, Otte et al showed that probiotics were able to regulate COX-2 gene expression significantly in comparison to heat inactivated probiotics.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%